MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA TEMA 6 ENERGI DAN PERUBAHANNYA MELALUI PENERAPAN MODEL PROJECT BASED LEARNING DAN MEDIA POWTOON DI SEKOLAH DASAR - Tesar Dwi Saputra; R.Teti Rostikawati; Siti Nurjanah (STKIP Subang, 2023)
The purpose of this study was to improve learning outcomes for students by using the Project Based Learning learning model for class III-D students at SDN Bondongan, Bogor City, semester II of the 2022/2023 school year. The research used is Collaborative Classroom Action Research (PTKK) which is qualitative descriptive using a qualitative approach and validated using a quantitative approach by collecting data at SDN Bondongan, Bogor City. The subjects of this research were students of class III-D SDN Bondongan Kota Bogor with a total of 27 students, 15 girls and 12 boys. The object of this research is the improvement of student learning outcomes on Theme 6: Energy and its Changes in mathematics subjects using the Project Based Learning learning model and the use of powtoon media. This research was conducted in two cycles and through four stages which include: planning, implementation, observation and reflection. Data were obtained through observation, learning implementation, direct tests and documentation. The results of this study indicate that the application of the Project Based Learning learning model can improve student learning outcomes. The increase in student learning outcomes can be measured from the evaluation results of cycle I and cycle II with an increase in student learning outcomes that have met the achievement of learning outcomes, namely in cycle I by 75.37% (12 students) and in cycle II by 84.63% (21 students). The results of research in class III-D at SDN Bondongan, Bogor City have been achieved well, namely there is an increase in learning outcomes by applying the Project Based Learning model and the use of powtoon media.